The Semantics Relation of Japanese Aspect -teiru and Negation - Maulia, Dini; Hariri, Tatang; Arimi, Sailal (Jurnal Arbitrer, 2023)
Verb aspects in the form of -teiru in Japanese is a category that is still common to be discussed as the result of meaning classification that is prompted. This article tries to explore the aspect relations in -teiru form toward negation to see the change of meaning that is produced. This way, the writer recommends the aspects classification of -teiru when it is present with a negation constituent in clause construction. The object of this research is the verb form -teiru in Japanese, the data are taken from Konotoha corpus in collecting the data, the writer used several keywords including -teiru, -teinai, -teita, -teinakatta, -teimasu, -teimasen, -teimashita, and -teimasendeshita. The aspect analysis of -teiru in this research refers to a theory that is explained by Nitta (1995) who classified the Japanese -teiru meaning in four categories, including: ugoki no saichuu ‘continuity of action’, kekkajoutai no jizoku ‘continuity of result state’, kurikaeshiteki jizoku ‘repeated continuity’, and keiken-kiroku ‘experience-note/memory’. Based on the data analysis, it shows that the presence of negation in both past and non-past can generate -teiru form which is later classified into two, they are perfective and imperfective. Those that are categorized as perfective aspect are the presence of negation on aspect meaning of -teiru within category kekkajoutai no jizoku. While the imperfective aspect occurs during the presence of negation within categories ugoki no saichuu, kurikaeshiteki jizoku, and keiken-kiroku.